193k views
4 votes
2(4x -4) + 8x = 2 (8x -3) solve for x please

User Leomar
by
6.1k points

1 Answer

7 votes

Answer:

No Solutions

Explanation:

Let's solve your equation step-by-step.

2(4x−4)+8x=2(8x−3)

Step 1: Simplify both sides of the equation.

2(4x−4)+8x=2(8x−3)

(2)(4x)+(2)(−4)+8x=(2)(8x)+(2)(−3)(Distribute)

8x+−8+8x=16x+−6

(8x+8x)+(−8)=16x−6(Combine Like Terms)

16x+−8=16x−6

16x−8=16x−6

Step 2: Subtract 16x from both sides.

16x−8−16x=16x−6−16x

−8=−6

Step 3: Add 8 to both sides.

−8+8=−6+8

0=2

Answer:

There are no solutions.

User Ned Ruggeri
by
6.3k points